The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2196/mhealth.9912
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Carrot Rewards App, a Population-Level Incentive-Based Intervention Promoting Step Counts Across Two Canadian Provinces: Quasi-Experimental Study

Abstract: BackgroundThe Carrot Rewards app was developed as part of an innovative public-private partnership to reward Canadians with loyalty points, exchangeable for retail goods, travel rewards, and groceries for engaging in healthy behaviors such as walking.ObjectiveThis study examined whether a multicomponent intervention including goal setting, graded tasks, biofeedback, and very small incentives tied to daily step goal achievement (assessed by built-in smartphone accelerometers) could increase physical activity in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 54 publications
3
90
0
Order By: Relevance
“…1) provided very small incentives for individualized daily step goal achievements. A three-month "Steps" evaluation was published in 2018 [30]. In this quasi-experimental study of users living in two Canadian provinces, Mitchell et al (2018) found average daily step count increased by 5% between baseline and the three-month assessment (115.70 steps; P < .001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) provided very small incentives for individualized daily step goal achievements. A three-month "Steps" evaluation was published in 2018 [30]. In this quasi-experimental study of users living in two Canadian provinces, Mitchell et al (2018) found average daily step count increased by 5% between baseline and the three-month assessment (115.70 steps; P < .001).…”
Section: Introductionmentioning
confidence: 99%
“…A three-month "Steps" evaluation was published in 2018 [30]. In this quasi-experimental study of users living in two Canadian provinces, Mitchell et al (2018) found average daily step count increased by 5% between baseline and the three-month assessment (115.70 steps; P < .001). A more pronounced 32% increase was observed among highly engaged, physically inactive users (1224.66 steps; P < .001).…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with a growing but still limited (to a small number of RCTs) evidence base suggesting that app exposure is paramount and that greater engagement may produce greater effects. [10][11][12]32 Limitations This study was not without limitations. The quasi-experimental design, for instance, makes it di cult to conclude with con dence that the Carrot Rewards STC feature caused an increase in PA. To increase internal validity in this real-world public health intervention context, we matched experimental participants with similar controls, used three main analytic approaches to address our primary objective and conducted two sensitivity analyses.…”
Section: Discussionmentioning
confidence: 93%
“…50 With nearly half of the Carrot Rewards users in general accumulating less than 5,000 steps per day, a mere 500 to 1,000 step increase from baseline values could have broad implications. 12 In fact, a recent 12 month analysis of the Carrot Rewards app suggests approximately 100,000 Canadians (or 0.3% of the Canadian population) moved up from the "physically inactive" category to the "moderately active" (5,000 to 7,500 steps per day). 34 Similar studies…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation